MINI DENTAL IMPLANT AS TREATMENT OF CHOICE IN A LATE TOOTH AVULSION WITH BONE RESORBTION: CASE REPORT - Hans Goenawan; Maria Goreti Widiastuti; Muhammad Fuadi; Rizqan Maulana (Fakultas Kedokteran Gigi Unjani, 2023)
Tooth avulsion is a severe condition of traumatic dental injury. The long-time effect of untreated tooth avulsion is alveolar bone loss. The mini dental implant can be a treatment for single tooth replacement in a late tooth avulsion with bone resorption. The purpose of this study is to present a case report of the mini dental implant in a late avulsion of an anterior maxillary tooth without bone augmentation. Thirty years old male patients came to clinic with the left upper central incisor avulsed due to a traffic accident three years before. There has been mild vertical and horizontal bone resorption and diastemas. He wanted to replace the missing tooth with a fixed denture, and the patient refused any bone augmentation. The mini dental implant was an alternative treatment for this case. Orthodontic treatment was performed to regain space before mini dental implant placement because some teeth had been migrated, causing some diastemas. After seven months of orthodontic treatment, we inserted a 3.0 x 13.0 mm nobel active implant bone level and installed the healing abutment. The prosthetic crown was screwed carefully using a manual torque wrench with a maximum torque force not exceeding 15 Ncm. The mini dental implant could be a treatment for a late avulsion case without bone augmentation. DOI : 10.54052/jhds.v2n3.p405-414